Soil Deformation around a Cylindrical Cavity under Drained Conditions: Theoretical Analysis. (29th June 2022) - Mabe Fogang, Pieride; Liu, Yang; Zhao, Jiale; Azeuda Ndonfack, Kevin Igor
Abstract : This paper proposes analytical solutions to the soil deformation around a cylindrical cavity under drained conditions. Analytical procedures are used to predict the degree of interaction between cavities and ground surface loads based on mathematical theorems. The stresses applied at the boundary condition induce the ground motions around the cylindrical cavity wall. Additionally, the Airy stresses are obtained through mathematical derivatives and integrations by combining the Fourier analysis test with the Navier equations. Next, we established a schematic representation of the horizontal and vertical displacement related to the corrective shear model to obtain insight into the intensity and directions of ground stresses. The resulting transformations include displacement, shear, and deviatoric stresses applied to the cylindrical cavity wall. These data can be used as input parameters for numerical simulations to alternatively solve the groundmass redistribution problems and calibrate the horizontal stress of drained soil conditions.